Investigating red pigment production by Penicillium purpurogenum DSM 62866 - Horn, Caryn (Centre for Bioprocess Engineering Research, 2023)
The production of a diverse range of pigments with variable properties and application potential highlights filamentous fungi as potential sources of pigments in the consumer-driven move toward natural colourant alternatives in food, cosmetic and nutraceutical products. The majority of natural pigments currently in use are obtained from sources such as insects and plants, including fruit and vegetables. These sources are inherently affected by natural variation and seasonal availability. Fungal pigments can, however, be produced in large-scale processes, under optimised and controlled conditions, with minimal dependence on weather and seasonal raw materials. Penicillium purpurogenum was selected for investigation in this study on the basis of reported pigment production without the co-production of mycotoxins, and the ability to adjust pigmentation through modifying cultivation conditions. Red pigments produced by this organism are of particular interest given the demand for this colour in food and cosmetic applications. Red pigment production by P. purpurogenum DSM 62866 was confirmed on a medium composed of 30 g.L- 1 malt extract and 3 g.L-1 soya peptone (MESP medium), following which the impact of varying cultivation conditions was investigated. Factors considered included cultivation temperature, pH and the application of buffers, and shaking speed during incubation of flask cultures. Conditions identified as beneficial for pigment production and, therefore, applied to 5 L cultivation in a benchtop bioreactor, were a temperature of 30 °C and a culture pH of 5.0 maintained through the application of a 50 mM citrate buffer. The pH, growth and pigment production trends were consistent upon scaling up the cultivation from 100 mL shake flask to 5 L bioreactor scale. The volumetric biomass concentration achieved under these base case conditions in the bioreactor system was approximately 8.4 g.L -1 dry weight with a volumetric pigment concentration, based on absorbance at 500 nm, of 24 OD units. This related to a yield of pigment on biomass of 2.86 OD units.gx -1 . Maximum biomass productivity observed between approximately 30 and 120 hours of cultivation was determined to be 0.089 ± 0.007 gx.L-1 .h-1 , with maximum pigment productivity of 0.72 ± 0.18 OD units.h- 1 observed over the period of approximately 78 to 102 hours. Pigment production was estimated to start between 54 and 69 hours of cultivation. Using the Luedeking-Piret model of product formation, pigment production was shown to not be growth-associated. It is however, biomass associated and can be formed when the culture is actively growing. The non-growth associated specific pigment production rate, β, defining the base case cultivation was estimated at 0.23 OD units.gx -1 .h-1 . The pigmentation generated by P. purpurogenum DSM 62866 was shown to be the result of a mixture of multiple polar pigments. Extraction of pigment products was achieved using ethyl acetate, with intense red colouration still, however, observed in the aqueous medium. The pigment products in the organic and aqueous phases were processed further, with isolated products submitted for mass spectrometry analysis. A major red product present in the ethyl acetate extract was suggested to be an alanine derivative of the Monascus pigment rubropunctamine based on absorbance maxima and mass spectrometry analysis. The complex nature of the medium could support the formation of a number of related pigment derivatives with properties, such as solubility, dependent on incorporation of various side chains. Investigation of shaking speed during flask cultivation and agitation speed during benchtop bioreactor cultivation revealed a relationship between pigment production by P. purpurogenum and the rate of oxygen transfer into the cultivation medium. Residual oxygen concentration was demonstrated to not be a major factor affecting pigment production. A direct relationship was observed between pigmentation and kLa defining the system over the kLa range of 20 to 25 h -1 , corresponding to a maximum oxygen transfer rate of approximately 150 to 188 mg.L-1 .h-1 . During bioreactor cultivation, red pigmentation increased from 0 OD units to approximately 25 OD units as agitation speed was increased. Potential antioxidant properties of the pigment products could explain this trend. The impact of medium composition was also investigated over a range of growth scales, namely agar plate, multiwell plate, shake flask and bioreactor cultivation. Changes to medium composition included altering the ratio of malt extract to soya peptone and investigating the impact of replacing malt extract with a marshmallow-based substrate as a simple representation of a confectionery waste stream. Across growth scales, soya peptone was demonstrated to be an important medium component for pigment production. Replacing soya peptone with peptone of animal origin during agar plate cultivation inhibited pigment production by P. purpurogenum. The altered malt extract, soya peptone medium taken forward into bioreactor cultivation was composed of half the amount of malt extract, in comparison to the base case medium, with the concentration of soya peptone unchanged (Half MESP medium). This supported equivalent volumetric pigment concentrations, but approximately half the amount of biomass in comparison to MESP medium. As observed under base case conditions, scale-up from shake flasks to the bioreactor system using the Half MESP medium had little effect on volumetric biomass and pigment concentrations achieved. The highest specific pigment productivity was, therefore, achieved when cultivating P. purpurogenum on a medium composed of 15 g.L - 1 malt extract and 3 g.L - 1 soya peptone, maintained at a pH of 5 through the application of a citrate buffer, with a cultivation temperature of 30 °C. Yield of pigment on biomass was calculated to be 6.13 OD units.gx -1 , representing a 2.1-fold increase over the base case cultivation. Maximum biomass productivity was shown to be similar to that obtained in MESP medium at 0.077 ± 0.006 gx.L-1 .h- 1 , but over a shorter period of approximately 30 to 54 hours of cultivation. Maximum pigment productivity was, however, observed over approximately the same period as that in the MESP medium and was defined by a value of 0.71 ± 0.11 OD units.h-1 . The β value in the Half MESP medium was significantly higher, at 0.98 OD units.gx -1 .h-1 , showing an increase over the base case value of 4.3-fold. When replacing the malt extract in the Half MESP medium weight-for-weight with marshmallow confectionery, to simulate a sugar-rich confectionery waste stream, growth and pigment production of P. purpurogenum was supported. Biomass concentration achieved was similar to that obtained in Half MESP medium, while the volumetric pigment concentration was significantly lower. The result was a yield of pigment on biomass of 3.01 OD units.gx - 1 , which is similar to that obtained using the base case medium. The ability of this organism to grow and produce pigments when cultivated on this alternative substrate demonstrates an opportunity for improved resource efficiency through utilisation of waste resources for conversion to a product, thereby improving economic feasibility of the process. Potential exists for improving product yields through further optimisation or supplementation studies. When considering the combined results of the MESP, Half MESP and marshmallow-based medium cultivations, it was observed that sugar concentration in the medium was a determining factor for maximum volumetric biomass concentration achieved, but not for pigment productivity. Residual sugar concentration was also demonstrated to not be a trigger for the onset of pigmentation. Pigment production was seen to coincide with sporulation of the culture, indicating that some endogenous or external factor, such a medium composition, could be involved in the simultaneous onset of these two cellular processes. Medium components supplied were, however, shown to affect maximum volumetric pigment concentration. This could be attributed to the presence of a growth factor, or equivalent component, in the malt extract or soya peptone. Given the high pigment productivity achieved in this study when using a malt extract and soya peptone based medium, P. purpurogenum DSM 62866 is a promising candidate for the production of natural colourant alternatives. Further work should focus on downstream processing and formulation as well as investigating pigment properties which are important considerations for commercialisation, such as stability and ease of application.